Better data management, one nudge at a time - Daria Orlowska; Colleen Fallaw; Yali Feng; Livia Garza; Ashley Hetrick; Heidi Imker; Hoa Luong (IASSIST Quarterly, 2021)
How do you help people improve their data management skills? For our team at the University of Illinois at Urbana-Champaign, we decided the answer was "one nudge at a time”.